2017
DOI: 10.1002/2017jb014320
|View full text |Cite
|
Sign up to set email alerts
|

Uplift and denudation history of the Akaishi Range, a thrust block formed by arc‐arc collision in central Japan: Insights from low‐temperature thermochronometry and thermokinematic modeling

Abstract: Fission track (FT), (U‐Th)/He (He), and U‐Pb data were used to identify the denudation history of the Akaishi Range, central Japan. The northern Akaishi Range is bounded on the east by the Itoigawa‐Shizuoka Tectonic Line Fault Zone (ISTL‐FZ). The thermochronometric ages progressively decrease with the decreasing distance to the ISTL‐FZ. Thermokinematic calculations suggest that the age pattern observed can be explained by 5–7.5 mm/yr reverse slip on the ISTL‐FZ that dips 34–45° west and soles onto detachment a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 103 publications
1
13
0
Order By: Relevance
“…The number of He data in the compilation is low, which would still be the case if the unpublished data were included, which were excluded from the compilation (Figure ). the He ages were only reported for the Tohoku region (Sueoka, Tagami, & Kohn, ; Sueoka, Tagami, Kohn, & Fukuda, ), Hida Range (Ahadi et al, ), Kiso Range (Sueoka et al, ), Akaishi Range (Sueoka et al, ; Sueoka et al, ), Tanzawa Mountains (Yamada & Tagami, ), Tono area (unpublished data), Taki area in the Kii Peninsula (Yamada et al, ), and Awaji Island (Ito, ). He ages were also obtained in the Kunashiri Island (De Grave et al, ), but the border of this region is disputed by Russia and Japan.…”
Section: Results and Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of He data in the compilation is low, which would still be the case if the unpublished data were included, which were excluded from the compilation (Figure ). the He ages were only reported for the Tohoku region (Sueoka, Tagami, & Kohn, ; Sueoka, Tagami, Kohn, & Fukuda, ), Hida Range (Ahadi et al, ), Kiso Range (Sueoka et al, ), Akaishi Range (Sueoka et al, ; Sueoka et al, ), Tanzawa Mountains (Yamada & Tagami, ), Tono area (unpublished data), Taki area in the Kii Peninsula (Yamada et al, ), and Awaji Island (Ito, ). He ages were also obtained in the Kunashiri Island (De Grave et al, ), but the border of this region is disputed by Russia and Japan.…”
Section: Results and Overviewmentioning
confidence: 99%
“…In this region, high mountains were formed in the Late Pliocene and Quaternary, which was mainly related to active faulting. Therefore, a substantial number of ages was obtained for reconstructing the uplift/denudation history of these mountains (e.g., Ito & Tanaka, 1999;Sueoka et al, 2012;Sueoka, Ikeda, et al, 2017;Yamada & Tagami, 2008). Many data were also reported for the area along the Pacific coast of the outer zone of the Southwest Japan, where the exhumation and evolution histories of the accretionary complexes have mainly been investigated (e.g., Hasebe et al, 1993;Hasebe & Tagami, 2001…”
Section: Legend Of Age Datamentioning
confidence: 99%
“…The SHRIMP U-Pb zircon age shows older age at the margin of the pluton and younger age in the center of the pluton indicative of crystallization start form the margin. Recently, a detailed thermochronological study by Sueoka et al (2017) reported zircon U-Pb age of 13.8-12.4 Ma, zircon fission-track age of 10.0-5.6 Ma, zircon (U-Th)/He age of 8.8-3.4 Ma and apatite fission-track age of 8.2-3.1 Ma.…”
Section: The Kaikomagatake Plutonmentioning
confidence: 99%
“…1b). Recently, precise low-temperature thermochronological study with thermokinematic modeling has been performed on the Kaikomagatake pluton (Sueoka et al, 2017), illustrating the denudation history of the Akaishi Range where the pluton is distributed. Therefore, estimation of emplacement depth of the Kaikomagatake pluton will provide petrological constraints on its denudation history, which in turn will be an important information on revealing tectonic evolution of the Izu collision zone.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation